From model organism to application: Bacteria-induced growth and development of the green seaweed Ulva and the potential of microbe leveraging in algal aquaculture - Wichard, Thomas (Seminars in cell & developmental biology, 2023)
The marine green macroalga Ulva (Chlorophyta, Ulvales), also known as sea lettuce, coexists with a diverse microbiome. Many Ulva species proliferate in nature and form green algal blooms (“green tides”), which can occur when nutrient-rich wastewater from agricultural or densely populated areas is flushed into the sea. Bacteria are necessary for the adhesion of Ulva to its substrate, its growth, and the development of its blade morphology. In the absence of certain bacteria, Ulva mutabilis develops into a callus-like morphotype. However, with the addition of the necessary marine bacteria, the entire morphogenesis can be restored. Surprisingly, just two bacteria isolated from U. mutabilis are sufficient for inducing morphogenesis and establishing the reductionist system of a tripartite community. While one bacterial strain causes algal blade cell division, another causes the differentiation of basal cells into a rhizoid and supports cell wall formation because of a low concentration of the morphogen thallusin (below 10-10 mol/L). This review focuses on the research conducted on this topic since 2015, discusses how U. mutabilis has developed into a model organism in chemical ecology, and explores the questions that have already been addressed and the perspectives that a reductionist model system allows. In particular, the field of systems biology will achieve a comprehensive, quantitative understanding of the dynamic interactions between Ulva and its associated bacteria to better predict the behavior of the system as a whole. The reductionist approach has enabled the study of the bacteria-induced morphogenesis of Ulva. Specific questions regarding the optimization of cultivation conditions as well as the yield of raw materials for the food and animal feed industries can be answered in the laboratory and through applied science. Genome sequencing, the improvement of genetic engineering tools, and the first promising attempts to leverage macroalgae–microbe interactions in aquaculture make this model organism, which has a comparatively short parthenogenetic life cycle, attractive for both fundamental and applied research. The reviewed research paves the way for the synthetic biology of macroalgae-associated microbiomes in sustainable aquacultures. •The macroalga Ulva mutabilis was established as a model system in chemical ecology.•Cross-kingdom interactions foster symbiosis between Ulva and associated bacteria.•Bacteria provide Ulva with algal growth and morphogenesis promoting factors.•The morphogen thallusin induces rhizoid and cell wall formation in Ulva.•Microbiome leveraging and engineering are useful for aquaculture maintenance and optimization.